2013
DOI: 10.1620/tjem.229.115
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Micronuclei Frequency in Peripheral Blood Lymphocytes and Retention of 131-I in Thyroid Cancer Patients

Abstract: Differentiated thyroid cancers (DTCs) derive from thyroid follicular cells and include papillary and follicular cancers. In patients with DTCs, the initial treatment includes thyroidectomy and radioactive iodine (131-I) therapy. The objective of this study was to examine whether the intensity of DNA damage in peripheral blood lymphocytes (PBLs) of DTC patients depends on the amount of 131-I retained in the selected regions of interest (thyroid and abdominal region) as well as in the whole-body 72 hours after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The CBMN assay applied to peripheral blood lymphocytes is a standard cytogenetic technique for genetic toxicology and biological dosimetry that provides good reliability and reproducibility without requiring a high level of expertise. The existing tools for the automation of MN scoring permits large-scale use of the CBMN assay not only for regulatory testing in genetic toxicology [1], but also in the field of radiation protection to assess medical [32,33] or professional exposure [14].…”
Section: Discussionmentioning
confidence: 99%
“…The CBMN assay applied to peripheral blood lymphocytes is a standard cytogenetic technique for genetic toxicology and biological dosimetry that provides good reliability and reproducibility without requiring a high level of expertise. The existing tools for the automation of MN scoring permits large-scale use of the CBMN assay not only for regulatory testing in genetic toxicology [1], but also in the field of radiation protection to assess medical [32,33] or professional exposure [14].…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation between micronuclei frequency and the level of platelets without correlation to thyroid-related hormones has been observed in blood of patients suffering from differentiated thyroid cancer and treated with radioactive iodine ( 131 I) [65]. Dom et al [66] studied children exposed and non-exposed to the Chernobyl radiation and compared them in the transcriptomes of normal contralateral tissues of PTC; in this way, the authors identified a gene expression signature (793 probes) that permits discrimination between both cohorts.…”
Section: Biomarkers Of Thyroid Damagementioning
confidence: 99%
“…Radioiodine therapy usually reduces the antioxidants and antioxidative enzymes in the body that leads to increased MDA level (29) . Vrndic et al (30) reported significant increase in serum MDA level from 2 days up to a week after RAIT, but Alavi et al (28) observed a significant increase in MDA level on 3rd day after RAIT. Males were found more susceptible to oxidative stress induced by RAIT as compared to females.…”
Section: Discussionmentioning
confidence: 95%